2015
DOI: 10.1007/s12035-015-9241-z
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Promotes Oligodendroglial Differentiation Through Inhibition of Wnt Signaling Pathway

Abstract: Aspirin, one of the most commonly used anti-inflammatory drugs, has been recently reported to display multiple effects in the central nervous system (CNS), including neuroprotection and upregulation of ciliary neurotrophic factor (CNTF) expression in astrocytes. Although it was most recently reported that aspirin could promote the proliferation and differentiation of oligodendrocyte precursor cells (OPCs) after white matter lesion, the underlying mechanisms remain unclear. To dissect the effects of aspirin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Previous studies have reported that aspirin affects cells through the JAK1/STAT1 pathway, ERK1/2 activation, and the canonical Wnt/β-catenin pathway [36][37][38][39]. Among these pathways, the canonical Wnt/β-catenin signaling pathway is a highly conserved pathway related to cell growth, development, metabolism, and stem cell maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that aspirin affects cells through the JAK1/STAT1 pathway, ERK1/2 activation, and the canonical Wnt/β-catenin pathway [36][37][38][39]. Among these pathways, the canonical Wnt/β-catenin signaling pathway is a highly conserved pathway related to cell growth, development, metabolism, and stem cell maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Co‐treatment with Aspirin and DHA suppressed activation of microglia in vitro and increased the microglial concentration of glutathione; therefore, increasing the antioxidant capacity of microglia cells (Pettit, Varsanyi, Tadros, & Vassiliou, ). Two studies using a combination of an in vivo model of white matter lesions and in vitro oligodendrocyte precursor cells demonstrated aspirin can protect white matter from insult (Chen et al, ; Huang et al, ). Aspirin appears to promote oligodendrocyte differentiation to repair white matter lesions possibly via inhibition of Wnt/β‐Catenin signalling, a regulator of cell fate.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of Wnt signaling also negatively regulates OL lineage development, including specification of OPCs from NSCs and terminal differentiation of OLs [42]. In addition, our previous work showed that selective activation of the Wnt/β-catenin signaling pathway by QS11 can suppress OL differentiation [43]. In line with the aforementioned findings, we showed here that QUE's effect on GSCs can also be attenuated by QS11, a selective agonist of the Wnt/β-catenin signaling pathway; this indicates that QUE-induced bioprocesses in GSCs are likely mediated via the Wnt signaling pathway and suggests a potential application of QUE to induce OL-oriented differentiation for enhanced effectiveness in chemotherapy of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Cells grown on coverslips were fixed with 4% paraformaldehyde for immunocytochemistry evaluation according to our previous study [43]. After being incubated with 1% bovine serum albumin (BSA)/0.3% Triton X-100 for 10 min to block non-specific reactions, cells were incubated with primary antibodies (see Table 1) overnight at 4°C followed by an incubation of secondary antibodies (see Table 2) for 2-3 h at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%